A obsolescência planejada no fomento do consumo (in)sustentável - Silva, Ramon Torres de Brito (2023)
We live in a culture of consumption, whose very human being has become a commodity. In it, the anthropocentric paradigm is present and the majority. This fact gave rise to the epistemic view of the separation between human beings and other biotic beings and abiotic elements. This made the biosphere to be seen as a great infinite amalgamation of resources that can be used at the pleasure of homo sapiens. Therefore, the limits of our planet are not respected, which ended up causing several socio-environmental harm - just look at exacerbated consumption (consumerism), the current coronavirus pandemic (COVID-19), as well as global warming. All this is maximized with the growing innovation, and stimulation of desires to be satisfied, caused by the technique of planned obsolescence (genre of species of programmed obsolescence of quality, utility and perceptibility). It is the basis of the linear production economy In this context, the national legal framework offered an answer to limit this status quo. For example, in the constitutional scope we find the promotion of sustainable consumption through the systematic interpretation of articles: 5th, item XXXII; 170, items V and VI, 225, caput, §1, items V and VI, all of the Federal Constitution of 1988. Considering that, in the infra-constitutional field, we have Law 8.078 of 1990, called the Consumer Defense Code, which endorsement of the constitutional scope adrede punctuated. In this context, the aim is to describe the culture of consumption as a promoter of planned/programmed obsolescence, thus clarifying the elements that can be modified in favor of the existence of an ecologically balanced environment. This objective is guided and supported by the hermeneutic methodological approach, which provides paradigms for the interpretative exercise of a textual character, inferring and limiting concepts and definitions. Therefore, the research shows itself as descriptive, qualitative in nature, with its bibliographic survey based on books, journal and specialized article. In this line of intellection, in harmony with the hermeneutic approach, here it uses the theoretical-conceptual procedural method, which enables the knowledge, work, improvement and monitoring of the state of the art of the fematics in question. Faced with such a conjuncture, it is expected to contribute to the awareness of consumers about their consumption practices, reducing the deleterious effects caused to the environment by consumerism motivated by planned obsolescence.